Peran Serta Masyarakat Dalam Upaya Pencegahan HIV AIDS Di Kelurahan Kalumpang - Tutik Lestari; Ridwan Yamko; Mudini Muhlis (UNIB Press, 2023)
In Indonesia the development of the spread of HIV AIDS every year shows an increase. Many efforts have been made involving all stakeholders and even the community to reduce the rate of spread of this disease, but there is no sign that this epidemic will end. HIV AIDS prevention has been regulated through a Minister of Health Regulation, where the involvement of community participation in efforts to prevent and control HIV AIDS through AIDS Care Citizens. Objective: to empower the community through the establishment of WPA in support of the HIV AIDS prevention program at the sub-district level. Method: activities through training involving representatives of community leaders and youth. Result: establishment of WPA Kalumpang Village consisting of 20 representatives of community leaders (health cadres, RT) and youth. Conclusion: community empowerment through WPA to prevent HIV AIDS transmission and HIV AIDS prevention at the Kalumpang Village level.